TINJAUAN YURIDIS TERHADAP TINDAK PIDANA PENCEMARAN BAKU MUTU LINGKUNGAN HIDUP DALAM UNDANG - UNDANG NOMOR. 32 TAHUN 2009 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP - Rika Oktariani (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACT  Rika Oktariani on tittle crime juridical revew against environmental quality pollution standard. Based on caonstitution no 32 on 2009 about protection and environmental management. Guided by Mrs Kunti Widayanti SH, M.Hum as the first advisor and Mr Syamsul Bahri SH, M.Hum as the second advisor.The backround of this research is purpose to know about environment problem. Problem of pollution and nvironmental destruction are things need serious attenion. Especially on environmental quality standard were damaged and contaminated and we can also know the environmental quality standard. Comprising water quality standard, waste water quality standard, seawater quality standard, ambient air quality standard, emmisions qualiy standard,derangement quality standard and other according of science and technology development besides that to know about the factors cause of environment pollution. We can also find out how legal action against criminal offenses environment living standard of the quality standard set in constitution no 32 on 2009 about protection and management the environment.The participation of the goverment trough environment care institution to gives control and protection of the environment and make an efforts to prevention of problems. According constitution no 32 on 2009 regarding the environment explained that efforts to address the problems of pollution consisting of preventive measures against pollution problemd to the problems of pollutions consists of prevention and control measures. Because the environment is a gift from God that is should be we keeps and preserves that in good quality cacn enjoy. Keywords :     Environment and Quality Standards Act – Law  Number. 32 of 2009 on the Protection and Environmental Management.